No time for composting: Subjective time pressure as a barrier to citizen engagement in curbside composting. (15th May 2019) - Wu, Wei-Ning; Liu, Li-Yin; Brough, Christopher
Highlights: Subjective indicator of time pressures is a better predictor. People who claim they lack time are less likely to use their composting cart. Larger households are more likely to engage in organic waste diversion. Older individuals are more likely to engage in organic waste diversion. Logistic regression was estimated to analyze the San Francisco City/County Survey. Abstract: Citizen engagement in waste management and recycling programs is crucial in achieving environmental sustainability. Existing studies have explored the determinants of waste management and recycling behavior as well as the adoption of selected waste management and recycling programs at both the individual and organizational levels. However, existing research has not explored, from a civic engagement perspective, why individuals who possess selected waste management and recycling tools fail to use them. Through individual level analysis, this study examines the reasons why residents fail to use their green curbside composting carts. Results indicate that subjective time pressure explains why individuals do not use their composting carts. Additionally, age and household size have different effects on the failure to use green curbside composting carts.